THE GREAT BUSTARD (OTIS TARDA L.) POPULATION DYNAMICS IN ROMANIA - SORIN GEACU* (Revue Roumaine de Géographie)
The paper based on archive material and field investigations, is a synthesis of the Great Bustard (Otis tarda L.) population dynamics in Romania, with focus on 1950, the year since when systematic observations on the species do exists. Besides, the chronological numerical evolution, and the complex causes responsible for the decline of this steppe bird, currently close to extinction in Romania, are also discussed. Not only is the Great Bustard listed among relict species, but also among the critically endangered ones.